Hyperandrogenemia impairs endometrial vitamin D receptor expression in polycystic ovary syndrome - Nur D. Gungor; Onder Celik; Ulun Ulug; Nilufer Celik; Aynur Ersahin; Kagan Gungor; Arzu Yurci; Meltem Yardim; Murat Kobaner; Ahmet Tektemur; Tuncay Kuloglu; Ivan Ilkov, Maslarski; et al. (Gynecological Endocrinology)
Objectives To determine the effects of hyperandrogenemia and other phenotypic parameters on endometrial vitamin D receptor (VDR-X2 and VDR-X4) expression in women with polycystic ovary syndrome (PCOS) undergoing ovarian stimulation and total embryo freezing.Methods Forty-four PCOS patients were divided into four phenotypes according to the criteria for hyperandrogenemia (HA), ovulatory dysfunction (OD), and polycystic ovary morphology (PCOM): phenotype A (HA+OD+PCOM), phenotype B (HA+OD), phenotype C (HA+PCOM), and phenotype D (OD+PCOM). Endometrial VDR expression was determined by real-time PCR and immunohistochemistry. Twenty age- and body mass index (BMI)-matched couples with male infertility were included as controls.Results VDR-X2 and VDR-X4 expression levels were significantly lower in the PCOS group than in the control group. A significant downregulation was detected in the relative VDR-X2 and X4 expression in phenotypes A, B, and C compared to the control group. VDR-X2 and X4 expression in phenotype D was significantly higher than in phenotypes A and B. A significant negative correlation was detected among VDR-X2, VDR-X4, serum testosterone (T), androstenedione (A), DHEAS, and insulin resistance (IR). Multivariate analysis revealed that serum T, A, DHEAS, and IR levels were independently associated with both VDR-X2 and VDR X4 relative gene expression after adjusting for age and BMI. The VDR mRNA and immunoreactivity of each phenotype overlapped. The clinical pregnancy rates for each phenotype were similar.Conclusion VDR expression in the endometria of patients with PCOS was defective. Hyperandrogenemia and insulin resistance are the key drivers of defective VDR expression in the endometrium of patients with PCOS.